A history of experimental phasing in macromolecular crystallography. Issue 3 (1st March 2016) - Isaacs, Neil
Abstract : The development of phasing methods in protein crystallography is presented. Abstract : It was just over a century ago that W. L. Bragg published a paper describing the first crystal structures to be determined using X‐ray diffraction data. These structures were obtained from considerations of X‐ray diffraction (Bragg equation), crystallography (crystal lattices and symmetry) and the scattering power of different atoms. Although W. H. Bragg proposed soon afterwards, in 1915, that the periodic electron density in crystals could be analysed using Fourier transforms, it took some decades before experimental phasing methods were developed. Many scientists contributed to this development and this paper presents the author's own perspective on this history. There will be other perspectives, so what follows is a history, rather than the history, of experimental phasing.